Inheritance studies of Maydis leaf blight resistance in early maturing genotypes of maize - Sharma, Preeti; Kamboj, M C; Punia, M S (Indian Journal of Plant Protection, 2020)
Studies on inheritance of the Maydis leaf blight (MLB) caused by Bipolaris maydis were conducted using six generations derived from 3 susceptible (HKI 209, HKI 1332, HKI 325-17AN) and 2 resistant inbred lines (HKI 1128, HKI 163). The genetic materials for field evaluation comprised of six generations i.e. 5 parental inbred lines (P1 and P2), 6 F1s, their F2s and back crosses (BC1 and BC2) of six crosses were studied for reaction to maydis leaf blight at CCS, HAU Regional Research Station, Karnal, during Kharif 2014. Partitioning of genetic effects into additive, dominance and epistatic components in this study indicated that resistance is predominantly attributed to significant additive effects along with significant presence of dominant and epistasis effects except in two crosses HKI 209 Ã— HKI 163 and HKI 325-17AN Ã— HKI 163 where only additive effects were significant along with epistatic interactions. In cross HKI 325-17AN Ã— HKI 1128, it was observed that six parameter failed to show any of the significant digenic interaction. This might be due to the presence of trigenic or higher order interaction or GÃ—E interaction or linkage. In cross HKI 209 Ã— HKI 163, the non-significant value of h (dominance) and significant value of â€œlâ€ showed the dispersal of alleles in the parents of this cross. The magnitude of additive component was relatively higher than non-additive component in the six crosses, suggesting that resistance to maydis leaf blight was largely governed by additive gene action. In cross HKI 1332 Ã— HKI 163, dominance (h) and dominance Ã— dominance (l) components had opposite signs indicating duplicate epistatis suggested chance of getting transgres sive segregants in the succeeding generations. Gene interactions and environment were also found to be important. Low to high heritability estimates were observed with good genetic advance. The higher estimates of additive component of variance, heritability and genetic advance indicated that selection for maydis leaf blight resistance is likely to be more effective. Population improvement approach, preferably, reciprocal recurrent selection may be followed for the development of early maturing and maydis leaf blight resistant cultivars of maize. Selection and heterosis breeding methods can be used to exploit fixable and non-fixable gene action for development of maydis leaf blight resistant populations of maize.